Pertimbangan Hakim dalam Putusan Kasus Gratifikasi yang Dilakukan Pejabat Daerah Kabupaten Tulungagung (Putusan Nomor 17 pid.Sus-TPK/2020/PN SBY) - Widyastuti, Nanik (Jurnal Ilmiah Wahana Pendidikan, 2024)
The main objective of this research is to analyze and examine what is considered by the judge in deciding the suspect in the crime of gratuity in decision Number 17 Pid.Sus-TPK/2020/PN.SBY. The research findings relate to the Strength of Evidence in giving decisions against the perpetrators of the Crime of Gratification in DECISION NUMBER: 17 Pid.Sus-TPK/2020/PN.SBY and Judges' Considerations in Giving Decisions to regional officials who carry out gratification cases (STUDY OF DECISION NUMBER: 17 Pid.Sus-TPK/2020/PN.SBY . Discussion I: Proof has an important position as a process to convince the judge about the truth of the arguments or arguments put forward in a dispute. It is proven that the argument can convince the judge and correlate with the granting of a request. Discussion II: Judges in trying a case carry out several stages, namely accepting, examining, and deciding criminal cases based on the principles of freedom, honesty and impartiality according to the method stipulated in the Criminal Procedure Code, namely examining based on evidence provided Enough. The judge in this case though has to examine every piece of evidence, analyze it, finally determine a decision on a case on the basis of law and justice In line with the conclusions above, it is hoped that the problems related to the discussion above in making decisions on several cases of criminal acts of gratification that were found guilty by judges prioritized considerations that are juridical in nature rather than those that are non-juridical in nature. The judge's decision is basically a work of finding the law, namely determining how according to the law should be in every event that concerns life in a rule of law. Because the judge's consideration is based on the factors revealed in the trial.